2023
DOI: 10.1172/jci163808
|View full text |Cite
|
Sign up to set email alerts
|

TMEM16E regulates endothelial cell procoagulant activity and thrombosis

Abstract: Endothelial cells (ECs) are constitutively an anticoagulant surface but switch to support coagulation following pathogenic stimuli. This switch promotes thrombotic cardiovascular disease. To generate thrombin at physiologic rates, coagulation proteins assemble on a membrane containing anionic phospholipid, most notably phosphatidylserine (PS). PS can be rapidly externalized to the outer cell membrane leaflet by phospholipid "scramblases", such as TMEM16F. TMEM16F-dependent PS externalization is well-characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…An intriguing finding of Schmaier et al is the absence of additive suppression for factor Xa generation following dual silencing of TMEM16E and TMEM16F ( 15 ). Thus, TMEM16E and TMEM16F appear to be epistatic to one another or to function in a linear pathway.…”
Section: Tmem16e and Tmem16f Promote Endothelial Cell Procoagulant Ac...mentioning
confidence: 99%
See 3 more Smart Citations
“…An intriguing finding of Schmaier et al is the absence of additive suppression for factor Xa generation following dual silencing of TMEM16E and TMEM16F ( 15 ). Thus, TMEM16E and TMEM16F appear to be epistatic to one another or to function in a linear pathway.…”
Section: Tmem16e and Tmem16f Promote Endothelial Cell Procoagulant Ac...mentioning
confidence: 99%
“…In this issue of the JCI , Schmaier and coauthors identified five proteins as important regulators of factor VIIa–catalyzed activation of factor X in TNF-α–stimulated human umbilical vein endothelial cells (HUVECs), including TMEM16F, TMEM16E, the closest paralog of the canonical Ca 2+ -activated scramblase TMEM16F ( 6 ), and Xkr9, a member of the Xk-related family of caspase-activated phospholipid scramblases ( 15 ). Expression of TMEM16E and TMEM16F was confirmed in unstimulated HUVECs and primary endothelial cells from human coronary artery and microvascular tissue, whereas XKR9 expression was undetectable with quantitative PCR (qPCR) in these cell types.…”
Section: Tmem16e and Tmem16f Promote Endothelial Cell Procoagulant Ac...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, inactivating mutations of TMEM16F result in Scott's syndrome, a bleeding disorder in humans (Millington‐Burgess & Harper, 2020). Recently, TMEM16F had been identified that could regulate PCA of EC by mediating PS exposure (Schmaier et al, 2023). Therefore, further investigation of the role and the molecular mechanism of TMEM16F‐mediated PS exposure in hyperlipidemia is necessary.…”
Section: Introductionmentioning
confidence: 99%